ON PARTICLE WAVES SOLUTIONS OF THE EQUATION OF ETHER WAVES - Zareski, David (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In previous publications, we demonstrated that the monochromatic waves Î¾ associated to particles,Â (including photons), submitted to forces, (gravitational regarding the photons), are the solutions of the ether elasticÂ wave equation for sufficiently large pulsation Ï‰. In these publications we did not considered the fact that it mayÂ exist waves Î¾ that are the solutions of this wave equation even for small values of Ï‰, like for example wavesÂ associated to the free photons. In the present paper, we show cases where waves Î¾ associated to particles submitted to forces are solutions of this ether wave equation for any values of Ï‰, i.e., even for its small values.